1994
DOI: 10.1121/1.408355
|View full text |Cite
|
Sign up to set email alerts
|

Loss factor height and width limits for polymer relaxations

Abstract: Polymer relaxations at the glass transition are often used in damping applications. Questions arise whether there is any limit to the height and width of the damping peak that can be achieved. A related question is whether there are any limits on the combination of these two properties that are achievable. This later question arises because of the experimental observation that the height of the peak is inversely related to the width of the peak. In this paper, these questions are addressed using various analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Moreover, as noted earlier, an accurate description for the frequency dependence of damping in the dissipative interphase may be provided by the Havriliak-Negami model [60]. Hartmann et al [61], reported all the input parameters necessary for a complete description of viscoelastic material properties for a set of polyurethane polymers within the context of Havriliak-Negami theory. The HN fitting parameters for two selected polymers with distinctively different damping properties in the frequency range of interest are listed in Table 2.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as noted earlier, an accurate description for the frequency dependence of damping in the dissipative interphase may be provided by the Havriliak-Negami model [60]. Hartmann et al [61], reported all the input parameters necessary for a complete description of viscoelastic material properties for a set of polyurethane polymers within the context of Havriliak-Negami theory. The HN fitting parameters for two selected polymers with distinctively different damping properties in the frequency range of interest are listed in Table 2.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…An appropriate description for the frequency dependence of the complex modulus of polymers in the glass transition region is given by HavriliakNegami model [60,61]. According to HN model, the real and imaginary parts of the complex modulus are given by [61]:…”
Section: Interphase Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Hartman, G. Lee, and J. Lee [14] have had success in fitting polyurethane CM data using the polynomial…”
Section: The Basic Fractional Modelmentioning
confidence: 99%
“…This fact is clear from a comparison of equations (6b) and (20). The relation between the magnitude and width of the loss factor peak for the Havriliak}Negami model was investigated in the work of Hartmann et al [14]. The authors determined the conjugate values of the loss factor and half-width by varying the exponent for "xed values of G /G and , and the inverse relation between K and = E was found.…”
mentioning
confidence: 98%